NEW RECORD OF Synhimantus (Dispharynx) nasuta (RUDOLPHI, 1819) CHABAUD, 1975 (NEMATODA, ACUARIOIDEA) IN THE YELLOW VENTED BULBUL (Pycnonotus goivier) FROM EAST KALIMANTAN, INDONESIA - Kartika Dewi; Mohammad Irham; Dewi M. Prawiradilaga; Kazuto Kawakami (BRIN Publishing (Penerbit BRIN), 2006)
Abstract not available